The effects of celebrity endorsement on consumers purchasing intentions - Carvalho, António Filipe Esteves Miguel de (2012)
The present thesis is a research about a marketing strategy: celebrity endorsement. Despite the fact that celebrity endorsement brings up some risks, it has been used quite extensively in the present era and it is a method to reach competitive advantage by companies. This dissertation focuses on examining the relationship between a set of variables: (1) gender, (2) credibility, (3) attractiveness, (4) type, (5) multiple endorsements and (6) multiple product endorsement that were identified during the literature review and consumers purchasing intentions. This relationship will spotlight Portuguese consumers and will use the Portuguese advertising industry as a contextualization, due to the fact that it was identified a lack of information about celebrity endorsement overall strategy in Portugal. The study in hand begins with a literature review which provides an insight into the research done by previous authors followed by an overview of last year’s Portuguese advertising campaigns. A quantitative approach has been adopted to investigate the relationship between the dependent and independent variables and 285 respondents have participated in the survey. Respondents answered two sets of questions after viewing an advertisement of a specific product featuring one or more endorsers. Results revealed that all the independent variables had a positive relation with consumers purchasing intentions, however some of them were quite low. Other findings of derived from analyzing the collected data resulted in some very interesting facts, which have been summarized in the conclusion, and also managerial implication relating to it has been discussed.